2013
DOI: 10.1089/scd.2012.0624
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Calcium Signaling Cascades in Human Embryonic Stem Cell-Derived Neural Precursors

Abstract: Human embryonic stem cell-derived neural precursors (hESC NPs) are considered to be a promising tool for cellbased therapy in central nervous system injuries and neurodegenerative diseases. The Ca 2 + ion is an important intracellular messenger essential for the regulation of various cellular functions. We investigated the role and physiology of Ca 2 + signaling to characterize the functional properties of CCTL14 hESC NPs during long-term maintenance in culture (in vitro). We analyzed changes in cytoplasmic Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 79 publications
3
40
0
Order By: Relevance
“…19 We then measured the intracellular calcium responses to ATP and carbachol in differentiated neurons plated in commercial PDL-coated 384-well plates with the rhVTN-N-supplemented medium. The EC 50 of the ATP and carbachol were 9.8 and 55.7nM, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19 We then measured the intracellular calcium responses to ATP and carbachol in differentiated neurons plated in commercial PDL-coated 384-well plates with the rhVTN-N-supplemented medium. The EC 50 of the ATP and carbachol were 9.8 and 55.7nM, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While cells and tissues differentiated from PSCs have been widely used for calcium signaling studies, we found only a limited number of data about such signaling in pluripotent stem cells, and even these data are mainly from mouse cell studies. Calcium signals in hESC-derived cardiomyocytes and neural cell types have been measured in most cases by calcium sensitive dyes: for cardiomyocytes Fura-2/AM [25][26][27][28], Fluo-4/AM [29,30] or dsRed+ [27], while for neural cell types Fluo-3/AM [8,31] Fura-2/AM [8,32] or Oregon green 488 Bapta-1 AM [33] have been applied. In pluripotent cells the application of Fluo-3/AM (mESC- [34], hESC- [8]) or Fluo-4/AM (mESC- [35][36][37], and hESC [12]) has been reported.…”
Section: Methods For Studying Calcium Signals In Human Ps Cellsmentioning
confidence: 99%
“…Generation of suitable human NPCs for neural differentiation and further transplantation is challenging because of the lack of standardized protocols and functional studies. Forostyak et al [32] and Viero et al [69] demonstrated that calcium signals in hPSC derived NPCs may reflect their regeneration capacity after transplantation. These NPCs exhibited spontaneous calcium oscillations and calcium signals evoked by high K+, ATP, glutamate, g-aminobutyric acid (GABA) and caffeine, indicating that the electrophysiological and calcium handling properties of NPCs are similar to those of matured neurons.…”
Section: Q7mentioning
confidence: 99%
“…To confront muscle cell diversity by considering how the activation mechanisms for generating Ca 2+ signals have been adapted to control the different cell functions, we utilized the intracellular free Ca 2+ measurement on single cells. For that purpose, a fluorescence microspectrofluorimetry was adapted so that the control and test solutions could be applied using a temperature controlled multichannel polypropylene capillary perfusion system (Forostyak et al 2013(Forostyak et al , 2016a(Forostyak et al , 2016b. A single outlet capillary tubing (100 μm inner diameter) with a flow rate of 250 μl/min was positioned close to the tested cell (<0.5 mm) and thus, the selected cell could be subjected to a constant flow of control buffer or test solutions.…”
Section: Introductionmentioning
confidence: 99%